Saving play : addressing standards through play-based learning in preschool and kindergarten - Rendon, Thomas; Gronlund, Gaye (St. Paul, MN : Redleaf Press, 2017)
'Play, academics, and standards can work together with the right strategies and support from educators. Take an active role in child-directed play to guide learning. Become a strong advocate for saving play in early childhood education by empowering teachers to join play and standards, and learn how child-led, open-ended play addresses the seven domains and Common Core Standards. This book is full of research and resources that link academic learning and play experiences. Engage in provocative questions for teachers and administrators to help you effectively share the importance of play in early learning with others, and help restore play to its proper role as both fun and educational. Gaye Gronlund, MA, is a nationally recognized consultant and author who works with early childhood programs across the country, specializing in developmentally appropriate practice, authentic assessment, play-based curriculum, and early learning standards. Her other publications include: Individualized Child-Focused Curriculum, Focused Observations, Second Edition, and Making Early Learning Standards Come Alive, Second Edition. Thomas Rendon is the coordinator of the Iowa Head Start State Collaboration Office and an active supporter of policy to promote play at a state level. He has an MBA from the University of Iowa and is currently working on a PhD in early childhood special education from Kent State University'--
'Saving Play addresses two questions critical to the field of early childhood education: Can child-directed, open-ended play activities in preschool and kindergarten classrooms address early learning and Common Core standards? and Can play be used to reach specific goals and objectives across all developmental domains? Authors Thomas Rendon and Gaye Gronlund answer both of these questions with a resounding yes and believe play, academics, and standards can and do work together'--
Includes bibliographical references and index.
Keywords: Play; Early childhood education -- Standards -- United States